Efficient heterologous expression, functional characterization and molecular modeling of annular seabream digestive phospholipase A2. (March 2018) - Smichi, Nabil; Othman, Houcemeddine; Achouri, Neila; Noiriel, Alexandre; Triki, Soumaya; Arondel, Vincent; Srairi-abid, Najet; Abousalham, Abdelkarim; Gargouri, Youssef; Miled, Nabil; Fendri, Ahmed
Graphical abstract: Highlights: Five fish digestive sPLA2 s cDNAs were synthesized by RT-PCR. Phylogenetic studies of fish sPLA2 s show a close homology to bird pancreatic sPLA2 s. The expressed AsPLA2 was highly purified and was found to be thermoactive. 3-D structure models of annular and white seabream sPLA2 s were built. The higher thermoactivity and phospholipids specificity of AsPLA2 was explained. Abstract: Here we report the cDNA cloning of a phospholipase A2 (PLA2 ) from five Sparidae species. The deduced amino acid sequences show high similarity with pancreatic PLA2 . In addition, a phylogenetic tree derived from alignment of various available sequences revealed that Sparidae PLA2 are closer to avian PLA2 group IB than to mammals' ones. In order to understand the structure-function relationships of these enzymes, we report here the recombinant expression in E.coli, the refolding and characterization of His-tagged annular seabream PLA2 (AsPLA2 ). A single Ni-affinity chromatography step was used to obtain a highly purified recombinant AsPLA2 with a molecular mass of 15 kDa as attested by gel electrophoresis and MALDI-TOF mass spectrometry data. The enzyme has a specific activity of 400 U.mg −1 measured on phosphatidylcholine at pH 8.5 and 50 °C. The enzyme high thermo-activity and thermo-stability make it a potential candidate in various biological applications. The 3D structure models of these enzymes were compared with structures of phylogenetically related pancreatic PLA2 . By following these models and utilizing molecular dynamics simulations, the resistance of the AsPLA2 at high temperatures was explained. Using the monomolecular film technique, AsPLA2 was found to be active on various phospholipids spread at the air/water interface at a surface pressure between 12 and 25 dyn cm −1 . Interestingly, this enzyme was shown to be mostly active on dilauroyl-phosphatidylglycerol monolayers and this behavior was confirmed by molecular docking and dynamics simulations analysis. The discovery of a thermo-active new member of Sparidae PLA2, provides new insights on structure-activity relationships of fish PLA2 .